THE INFLUENCE OF COMPETENCE, WORK MOTIVATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE IN CULINARY MSMES IN BANDUNG CITY - Yani Restiani Widjaja (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This study aims to describe the implementation of service activities in improving community knowledge, awareness, and participation through educational and practical approaches. The method used includes observation, preparation, implementation, and evaluation of activities. The results show that the service activities were carried out effectively and received positive responses from participants. The activity also contributed to improving participants’ understanding of the material presented. Therefore, this program is expected to be continued and developed as a sustainable effort to improve community quality and participation.